Repeated small-volume exchange transfusion for hyperleukocytosis in pediatric acute leukemia: A retrospective analysis - Dongxiu Zhang; Hailong Lin; Leting Huang (Frontiers in Pediatrics, 2023)
IntroductionLeukapheresis reduces hyperleukocytosis in children with acute leukemia. Although the usefulness of this procedure is under debate, a repeated small-volume exchange transfusion along with leukapheresis yielded satisfactory results.MethodsForty-seven patients with acute leukemia [32 acute lymphocytic leukemia (ALL) and 15 acute myeloblastic leukemia (AML)] were enrolled between January 2017 and June 2022 and underwent repeated small-volume exchange transfusion. The following were measured: demographic and clinical characteristics, time of the procedure, PWBC (peripheral white blood cell) count, hemoglobin, platelet count, blood biochemistry, electrolytes, coagulation, leukostasis, TLS (tumor lysis syndrome), DIC (disseminated intravascular coagulopathy), adverse events (AEs), and serious AEs (SAEs).ResultsThe demographic and clinical characteristics were not significantly different between ALL and AML patients, but differences were observed in PWBC counts (424.2 ± 135.6 vs. 223.8 ± 58.0 × 109/L). The procedures needed 3–8 processes, and the average procedure time was not significantly different between ALL and AML. The PWBC count gradually reduced to <100 × 109/L; hemoglobin, platelet count, K+, Na+, and Ca2+ were unchanged. Alanine aminotransferase, aspartate aminotransferase, total bilirubin, blood urea nitrogen, creatinine, troponin-I, creatine kinase-MB, prothrombin time, and activated partial thromboplastin time maintained normal or recovered from abnormal ranges. The manifestations of leukostasis, TLS, and DIC improved or disappeared. No AEs and SAEs occurred. The required total blood volume was based on initial PWBC count, manifestations of leukostasis, and age.ConclusionsOur finding suggests that repeated small-volume exchange transfusion is effective and safe for treating hyperleukocytosis in children with acute leukemia.